Use of thermal water as a natural coagulant for domestic wastewater sustainable treatment - Quintero-Jaramillo, Javier Andrés; Murillo-Arango, Walter; Cerón-Salazar, Ivonne Ximena (Universidad Pedagógica y Tecnológica de Colombia, 2017)
In the last several years, the interest on domestic wastewater treatment has increased due to the rise of water consumption resulted from the world population growth. The excessive use of inorganic coagulants, such as aluminum sulphate, in domestic wastewater treatment processes contributes to generate high negative environmental impacts and risks to living organisms. Besides its low biodegradability, as aluminum sulphate increases metal content in discharged effluents rises, generating toxic sludge. Therefore, searching for clean and sustainable processes for domestic wastewater treatment is important in order to reduce the pollutant discharges into fresh water bodies. In this paper, the potential use of thermal water as a natural coagulant for the domestic wastewater treatment from Manizales city (department of Caldas, Colombia), was studied. The effect of coagulant dose was analyzed and compared with the results of the conventional coagulants. Applying different doses of coagulants in domestic wastewater showed that the best coagulation activity was achieved by adding 35 ml/l of thermal water, and 140 mg/l of aluminum sulphate. In both cases, high turbidity removal efficiency (98.1 %) was achieved. The removal efficiency of Chemical Oxygen Demand (COD) using aluminum sulphate was 81.5 %, and using thermal water was 75.4 %. In conclusion, thermal water has positive coagulation properties; therefore, it is a promising alternative to aluminum sulphate as a natural coagulant on the treatment of domestic wastewater.